Apa yang Menyebabkan PT Sri Rejeki Isman Tbk Bangkrut? - Eva Lestari; Tiya Nurfauziah; Sari Rusmita (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the causes of bankruptcy of PT Sri Rejeki Isman Tbk (Sritex) by examining the influence of financial ratios on bankruptcy risk as measured by the Altman Z-score, while also considering the inflation rate as a control variable. Although Sritex once demonstrated sound financial performance, the company was officially declared bankrupt in 2025. This research employs a quantitative approach using multiple linear regression to test the relationship between liquidity, solvency, profitability, activity, and inflation rate on the Z-score. The data used consists of the company’s quarterly financial reports from 2014 to 2024, totaling 42 observations, analyzed using SPSS version 25. The results show that all four financial ratios (liquidity, solvency, profitability, and activity) significantly influence the Z-score, with the direction of influence aligning with financial and signaling theories. Liquidity, profitability, and activity have a positive effect on increasing the Z-score, while solvency has a significant negative effect. Conversely, the inflation variable does not significantly affect bankruptcy risk. These findings confirm that internal company factors reflected in financial ratios play a more dominant role in predicting bankruptcy compared to external factors. This study is expected to serve as a reference for management and investors in evaluating corporate financial risk more accurately and based on data.